Respuesta :

Answer:

[tex]\log\left(\dfrac{\sqrt{x}\:z^2}{4y^2}\right)[/tex]

Step-by-step explanation:

[tex]\dfrac12\log(x)-2\log(2y)+2\log(z)[/tex]

[tex]\textsf{Apply log power rule}: \quad n \log(x)=log(x)^n[/tex]

[tex]\implies \log(x)^{\frac12}-\log(2y)^2+\log(z)^2[/tex]

[tex]\textsf{Apply exponent rule}: \quad(ab)^c=a^cb^c[/tex]

[tex]\implies \log(\sqrt{x})-\log(4y^2)+\log(z^2)[/tex]

[tex]\textsf{Apply log quotient rule}: \quad \log(x)-\log(y)=log(\frac{x}{y})[/tex]

[tex]\implies \log\left(\dfrac{\sqrt{x}}{4y^2}\right)+\log(z^2)[/tex]

[tex]\textsf{Apply log product rule}: \quad \log(x)+\log(y)=log(xy)[/tex]

[tex]\implies \log\left(\dfrac{\sqrt{x}\:z^2}{4y^2}\right)[/tex]